Organising User Communities for Innovation Management - Schulz, Celine; SpringerLink (Online service) (Wiesbaden : Gabler, 2010)
Firms are increasingly realising the importance of social networks. Such networks of customers can play an essential role in assisting firms to organise and prioritise the pool of user information regarding their needs, feedback on existing products as well as ideas for new products. To profit from these communities, it is essential to understand why they exist, how they function and which goals they pursue. Based on survey data from users who are members in user groups of the management software firm Computer Associates, Celine Schulz examines how groups of users can be organised and leveraged by firms for their innovation processes.
Determinants of Sharing Information in User Communities -- Maximising Benefits from Participating in User Communities -- Selecting User Community Collaborators for Innovation Management -- Conclusion.
Keywords: Economics; Industrial management; Economics/Management Science; Management/Business for Professionals